LANGIT DAN BUMI PERSPEKTIF AL-QUR’AN DAN SAINS (Studi Komparatif Tafsir Al-Qurthubi, Tafsir Abdurrahman As-Sa’di, dan Sains Modern) - Iskhak Iskhak; Akmir Akmir; Nurfadillah Syam (Jurnal Ushuluddin Adab dan Dakwah, 2022)
Abstract This thesis research discusses the concept of heaven and earth based on the thoughts of al-Qurthubi, Abdurrahman as-Sa'di, and modern scientific theory. Which is listed in both the book of commentaries and books on modern science. The two commentary books are the book Al-Jami' li Ahkam Al-Qur'an and the book Taisiri Karimi ar-Rahman fi Tafsiri Kalami al-Mannan. The two interpretations were chosen because both of them have their own opinion regarding the concept of heaven and earth, with different life eras. The background of this research is that people are still debating about the existence and concept of heaven and earth in the name of the Qur'an and science. The focus of discussion in this research is matters relating to the process of creating the heavens and the earth/the process of forming the universe, the concepts and forms of the heavens and the earth, as well as the alternation of day and night/the concept of the motion of the heavenly and earthly bodies. The methodology used in this study is a qualitative approach to the type of library research. While the data analysis technique used is using descriptive comparative method or describing the three opinions regarding the concept of heaven and earth and also comparing the three opinions by looking at the differences and similarities. The results of this study indicate that al-Qurthubi, as-Sa'di and Modern Science have similarities and differences in terms of the concepts of heaven and earth. according to al-Qurthubi and as-Sa'di, the earth and the sky were created in six periods in the order of creation namely the earth then the mountains and the contents of the earth then the sky. Meanwhile, according to science, the sky was formed long before the earth. Besides that, al-Qurthubi said that the earth does not move, in this case it rotates. The third time the earth moves, there will be shocks/earthquakes as usual. According to him the earth is flat. Whereas as-Sa'di and modern science say that the earth is round. Al-Qurthubi and as-Sa'di also said that the circulation of the sun and moon causes day and night. Meanwhile, modern science says that it is the earth's rotation that causes the phenomenon of day and night.